The thermal structure and temporal evolution of high-enthalpy geothermal systems. (July 2016) - Scott, Samuel; Driesner, Thomas; Weis, Philipp
Highlights: Numerical models reveal the long-term evolution and thermal structure of high-enthalpy systems. Host rock permeability is a main control on whether systems are boiling below 1 km depth. Intrusion depth and the conditions of the brittle–ductile transition are further controls. Systems driven by a single intrusion may show multiple upflow plumes. We assess the implications of the models for geothermal exploration and field development. Abstract: Numerical modeling is a powerful tool to investigate the response of high-enthalpy geothermal systems to production, yet few studies have examined the long-term evolution and thermal structure of these systems. Here we report a series of numerical simulations of fluid flow and heat transfer around magmatic intrusions which reveal key features of the natural thermal and hydraulic structures of high-enthalpy geothermal systems. We explore the effect of key geologic controls, such as host rock permeability, the emplacement depth and geometry of the intrusion, and temperature-dependent permeability near the intrusion, on the depth and extent of boiling zones, the number and spatial configuration of upflow plumes, and how these aspects evolve over the systems' lifetime. Host rock permeability is a primary control on the general structure, temperature distribution and extent of boiling zones, as systems with high permeability (≥10 −14 m 2 ) show shallow boiling zones restricted to ≤1 km depth, while intermediate permeability (∼10 −15 m 2 ) systems display vertically extensive boiling zones reaching from the surface to the intrusion. Intrusion emplacement depth is a further control, as intermediate permeability systems driven by an intrusion at ≥3 km depth only show boiling above 1 km. If a cooling intrusion becomes permeable at temperatures significantly in excess of the critical temperature of water, the enthalpy of the upflow becomes high enough that systems with high permeability show vertically extensive boiling zones, and intermediate permeability systems spatially extensive zones of supercritical water near the intrusion. The development of multiple, spatially separated upflow plumes above a single intrusive body is characteristic of systems with high permeability and deep emplacement depth. Depending on the primary geologic controls, systems exhibit characteristic lateral and vertical gradients in pressure, temperature and enthalpy relative to the intrusive heat source which may aid in geothermal exploration and interpretation of field measurements.